Utilizing metagenomic next-generation sequencing and phylogenetic analysis to identify a rare pediatric case of Naegleria fowleri infection presenting with fulminant myocarditis - Lin, Liangkang; Luo, Lili; Wu, Mei; Chen, Jun; Liao, Yi; Zhang, Haiyang (Frontiers in Microbiology, 2024)
BackgroundNaegleria fowleri (N. fowleri), a rare and typically lethal amoeba, most commonly causes primary amoebic meningoencephalitis (PAM). This case report describes an exceptionally rare presentation of fulminant myocarditis as the primary manifestation in a 6-year-old child, diverging from the typical neurological pathogenesis associated with N. fowleri infection. Beyond neurological afflictions, the child developed arrhythmias and cardiac failure, necessitating treatment with extracorporeal membrane oxygenation (ECMO).MethodsDiagnosis was confirmed via metagenomic next-generation sequencing (mNGS) of both blood and cerebrospinal fluid (CSF). This analysis not only substantiated the infection but also revealed a potential new genotype of N. fowleri, designated k39_3, suggesting broader genetic diversity than previously recognized.ResultsImmediate treatment with Amphotericin B (Am B) and rifampin was initiated upon diagnosis. Despite aggressive management and supportive care, the patient failed to maintain hemodynamic stability, continued to show a decrease in cardiac output, and exhibited relentless progression of central nervous system failure, culminating in death within 72 h.ConclusionOur report documents a rare pediatric case of N. fowleri infection presenting with fulminant myocarditis, revealing an unexpected clinical manifestation and broadening the known spectrum of its effects. This emphasizes the need for enhanced surveillance and targeted research to understand the pathogenic mechanisms and improve treatment strategies.